Silent Bird Poisoning in Poland: Reconfirmation of Bromadiolone and Warfarin as the Proximal Causes Using GC-MS/MS-Based Methodology for Forensic Investigations - Damian Kobylarz; Łukasz Paprotny; Dorota Wianowska; Maciej Gnatowski; Kamil Jurowski (MDPI AG, 2024)
The extensive use of rodenticides poses a severe threat to non-target species, particularly birds of prey and scavengers. In this study, a GC-MS/MS-based method was used to unlock the cause of bird deaths in Poland. Organs (liver, heart, kidney, and lungs) collected during autopsies of two rooks (Corvus frugilegus) and one carrion crow (Corvus corone corone), as well as fecal samples, were analyzed for the presence of anticoagulant coumarin derivatives, i.e., warfarin and bromadiolone. As for warfarin, the highest concentration was found in crow samples overall, with concentrations in the feces and lungs at 5.812 ± 0.368 µg/g and 4.840 ± 0.256 µg/g, respectively. The heart showed the lowest concentration of this compound (0.128 ± 0.01 µg/g). In the case of bromadiolone, the highest concentration was recorded in the liver of a rook (16.659 ± 1.499 µg/g) and this concentration significantly exceeded the levels in the other samples. By revealing the reality of the threat, these discoveries emphasize the need to regulate and monitor the trade in rodenticides.